Health equity beyond borders: The demands of justice in global health - Go, JJQ (2023)
Health is widely regarded as being among our most valuable goods and highest ideals. At the same time, the contemporary state of global health makes for grim reading with immense suffering and deprivation across mortality and morbidity, especially within developing countries. This thesis is a work of political philosophy which takes seriously the complex reality of global injustice in our world today. It provides a comprehensive political philosophical account of what justice demands in the sphere of global health.